Men, sex & rape [videorecording] - Jennings, Peter; Leake, Craig; Yellin, Tom (ABC News, 1992)
Looks at some of the rape cases in Palm Beach, California. Jennings raises questions about men and their views on rape, women and what drives men to rape women.